Meaning in the animated children’s movie “Rabbids Invasion” - Kuntayuni Kuntayuni; Agus Darma Yoga Pratama (Universitas Lampung, 2022)
Audiovisual research is not only limited to an analysis of the translation applied to movies, but also about the meaning and how the aspects of that meaning can be well understood by the audience. The meaning of the movie refers to the verbal meaning and nonverbal meaning to see how the meaning of the movie is conveyed to the audience as a whole because verbal and nonverbal language basically has its own uniqueness in the process of conveying meaning. This study also aims to analyze the storyline to obtain the unity of verbal and nonverbal meanings in building the overall story in the movie. The research data chosen was the animated children’s movie “Rabbids Invansion” because it contains nonverbal signs which tend to be more than verbal language. Although there is verbal language, what appears refers to verbal language that is unknown or difficult to understand the meaning directly. The power of imagination in movie “Rabbids Invansion” is very strong. Therefore, the study of meaning in this movie becomes a very interesting and need to be analyzed in details. This research begins by listening to the movie, followed by collection data through screen recording techniques for data collection of visual or image aspects and taking a note for verbal language. The results of this study could later be useful for audiovisual researchers in producing a study in the field of meaning of children’s animated movie. Keywords: meaning, movie, image, verbal, nonverbal, plot.